2022
DOI: 10.1101/2022.02.05.22270499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study of immunogenicity and safety of Gam-COVID-Vac and Sinopharm BBIBP-CorV vaccines in Belarus

Abstract: Introduction: Lack of comparative studies on efficiency of a broad range of COVID19 vaccines leads to lower levels of adoption and subsequent lower total immunity in several regions, including Republic of Belarus. This clinical study captures and transparently demonstrates varying immunogenic responses to Sputnik V and Sinopharm vaccines. Aim of this study was: to compare the immunogenicity and reactogenicity of Sputnik V (Gam-COVID-Vac), RF and Sinopharm (BBIBP-CorV), PRC vaccines in vaccinated individuals. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The Pfizer vaccine was found to be superior to Sinopharm with respect to post-vaccination quantitative antibody titers (23). Similarly, the Sputnik V vaccine was also more immunogenic compared to Sinopharm (24). Regarding the Omicron variant, both Sinopharm and Janssen yielded significantly lower neutralizing activities compared to Pfizer and Moderna (25), and, this may explain that in our study, these vaccines showed a steeper decrease in efficacy over time.…”
Section: Discussionsupporting
confidence: 45%
“…The Pfizer vaccine was found to be superior to Sinopharm with respect to post-vaccination quantitative antibody titers (23). Similarly, the Sputnik V vaccine was also more immunogenic compared to Sinopharm (24). Regarding the Omicron variant, both Sinopharm and Janssen yielded significantly lower neutralizing activities compared to Pfizer and Moderna (25), and, this may explain that in our study, these vaccines showed a steeper decrease in efficacy over time.…”
Section: Discussionsupporting
confidence: 45%
“…These findings are not completely in line with ours, probably due to different time periods of observation and a later measurement of Ab levels in our study. A similar study conducted in Belarus, compared the immunogenicity and reactogenicity of Gam-COVID-Vac and BBIBP-CorV in 60 adults coming from the same population showing that the Gam-COVID-Vac vaccine was more immunogenic, and the BBIBP-CorV vaccine was less reactogenic [ 48 ]. Several studies investigated the immune response after application of the BNT162b2 vaccine as one of the widely administered SARS-CoV-2 vaccines worldwide, and even though high efficacy was announced after two doses of above 90% up to 6 months [ 49 ], an important long-term decline in Ab titers/levels was reported across several studies [ 14 , 19 , 20 , 38 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Pfizer vaccine was found to be superior to Sinopharm with respect to post-vaccination quantitative antibody titers (26). Similarly, the Sputnik V vaccine was also more immunogenic compared to Sinopharm (27).…”
Section: Discussionmentioning
confidence: 92%
“…The Pfizer vaccine was found to be superior to Sinopharm with respect to post-vaccination quantitative antibody titers (26). Similarly, the Sputnik V vaccine was also more immunogenic compared to Sinopharm (27). Regarding the Omicron variant, both Sinopharm and Janssen yielded significantly lower neutralizing activities compared to Pfizer and Moderna, (28) and, this may explain that in our study, these vaccines showed a steeper decrease in efficacy over time.…”
Section: Discussionmentioning
confidence: 99%